Establishment of diagnostic criteria for upper urinary tract urothelial carcinoma based on genome-wide DNA methylation analysis. Issue 12 (1st December 2020) - Fujimoto, Mao; Arai, Eri; Tsumura, Koji; Yotani, Takuya; Yamada, Yuriko; Takahashi, Yoriko; Maeshima, Akiko Miyagi; Fujimoto, Hiroyuki; Yoshida, Teruhiko; Kanai, Yae
ABSTRACT: The aim of this study was to develop a less invasive and accurate diagnostic system for upper urinary tract urothelial carcinoma (UTUC) based on genome-wide DNA methylation profiling. Genome-wide DNA methylation screening was performed using the Infinium HumanMethylation450 BeadChip, and DNA methylation quantification was verified using pyrosequencing. We analysed 26 samples of normal control urothelial tissue (C), an initial cohort of 62 samples (31 samples of non-cancerous urothelium [N] from UTUC patients and 31 samples of the corresponding UTUCs), a validation cohort of 82 samples (41 N and 41 UTUC samples), and 14 samples of urinary bladder urothelial carcinoma (BUC). In the initial cohort, we identified 2, 448 CpG sites showing significant differences in DNA methylation levels between both C and UTUC and N and UTUC, but not showing differences between C and N. Among these CpG sites, 10 were located within CpG islands or their shores and shelves included in genomic domains where DNA methylation levels are stably controlled, allowing discrimination of UTUC even from BUC. Receiver operating characteristic curve analysis for discrimination of UTUC from N in these 10 CpG and neighbouring sites (37 diagnostic panels in total) yielded area under the curve values of 0.959–1.000, with a sensitivity and specificity of 86.6–100% and 93.5–100%, respectively. The diagnostic impact was successfully confirmed in the validation cohort. Our criteria were useful for diagnosis of UTUC, regardless of its clinicopathological features. Application of our criteria to voided urine samples will ultimately allow non-invasive DNA methylation diagnosis of UTUC.